Estimation of energy usage in oil palm plantation at hilly area / Musthaffa Afifi Azmi - Azmi, Musthaffa Afifi (Faculty of Plantation and Agrotechnology, 2016)
This case study aims to estimate the energy usage and greenhouse gas (GHG) emission in oil palm plantation at hilly area. Energy that use from the machinery will affect the greenhouse gas (GHG) emission. An example of the gas emitted from the machinery is water vapour, carbon dioxide, methane, nitrous oxide, ozone and any fluorocarbons. This study was conducted with five different hilly areas in oil palm plantation in Malaysian that have the slope among 10°-60°. The data of field area, fuel consumption (1), the slope of topography and plant maturity was taken starting from Jan-December 2015. Based on the data collection, will determine to evaluate the overall energy use in the oil palm machinery operation and to estimate the quantity of C02 emitted from different field of oil palm. The result shows the hilly topography with different area and gradient of the slope impact for energy usage and GHG emission. The factors that contribute energy usage and C02 higher emitted at hilly area because of the weight of the transportation, great inertia, engine power and high rolling resistance. As the solution to decrease the emission of C02 and energy usage, replace the existing fuel to the biodiesel and better working planning schedule can be applied.